Deck Function 2: The Perceived Seamanship Competency of the Domestic Vessel on Board Trainees - Rex A. Abella, Chief Mate; Ian Mongaya, Chief Mate; Aranzado, Mst, Rey Q. (International Journal of Scientific Research and Management (IJSRM), 2022)
This study investigated the domestic vessel onboard trainees perceived seamanship competencies vis-à-vis the minimum requirements of STCW 1978 as amended in the Maritime Education College of the University of Cebu Lapu-Lapu and Mandaue. Categorically, this study determined the respondents' profile in terms of age, gender, type of domestic vessel boarded, and year completed academic requirements. Furthermore, it defined the perceived deck function 2 technical competencies, the relationship between the profile and the perceived competencies of the cadets, the significant difference in their technical competencies when grouped according to profiles, and the conclusion, recommendations, and the proposed action plan. The study used the descriptive-correlational method, and one hundred BSMT offshore domestic cadets were chosen as respondents. The study was conducted at the University of Cebu Lapu-Lapu and Mandaue. The researchers utilized an STCW-based checklist to gather the data needed. Frequency count, percent, Chi-square, and Kruskal-Wallis were used to treat the data collated. The study revealed a notable gap between the perceived competencies in ensuring satisfactory trim, stability, hogging, and sagging. It also determined a significant relationship between profile and gender and the perceived competencies. Moreover, the study showed no significant difference between the technical competencies when grouped according to profile. The results concluded that the success of producing quality seafarers is the primary responsibility of the maritime institute to ensure a globally competitive STCW '95 (Standards of Training, Certification, and Watchkeeping) compliant maritime education graduates.